2016
DOI: 10.1098/rsob.150276
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular redox homeostasis by the endocannabinoid system

Abstract: The endocannabinoid system (ECS) and reactive oxygen species (ROS) constitute two key cellular signalling systems that participate in the modulation of diverse cellular functions. Importantly, growing evidence suggests that cross-talk between these two prominent signalling systems acts to modulate functionality of the ECS as well as redox homeostasis in different cell types. Herein, we review and discuss evidence pertaining to ECS-induced regulation of ROS generating and scavenging mechanisms, as well as highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 123 publications
3
68
0
2
Order By: Relevance
“…Our findings are also in agreement with those of others (reviewed in Reference ) who describe the role of the eCB system in regulating ROS production and the redox state. Whereas several studies reported that activating the eCB system confers protection from oxidative stress, others demonstrated that its stimulation results in ROS generation and cell death .…”
Section: Disscussionsupporting
confidence: 93%
“…Our findings are also in agreement with those of others (reviewed in Reference ) who describe the role of the eCB system in regulating ROS production and the redox state. Whereas several studies reported that activating the eCB system confers protection from oxidative stress, others demonstrated that its stimulation results in ROS generation and cell death .…”
Section: Disscussionsupporting
confidence: 93%
“…It has been shown that both AEA and 2-AG can be synthesized in the plasma membrane. However, the degradation of phosphatidylinositol by phospholipase C results in the formation of a diacylglycerol precursor, whose hydrolysis (through diacylglycerol lipase activity, DAGL) allows the formation of 2-AG [80]. However, activation of DAGLα and DAGLβ requires GSH.…”
Section: Trp Receptorsmentioning
confidence: 99%
“…Importantly, these effects were prevented by a CB1 receptor antagonist [7]. Cannabinoid receptors have been shown to modulate the expression of pro-inflammatory cytokines [8]; the activation of CB1 receptors increases the level of pro-inflammatory cytokines, whereas activation of CB2 receptors promotes their reduction and generation of reactive oxygen species (ROS) [9]. Thus, endocannabinoids can simultaneously modify inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%